ABOUT INFLURNCE OF TENPERATURE GAS AND FUSION ON SIZE OF MICROGRANULES AT GAS DISPERSION - Ternovoy, Yurii; Lichkonenko, Natalya (Scientific Journal "Metallurgy", 2021)
Spraying liquid metals today is one of the most high-tech and productive methods forproducing high-quality metal powders. Earlier theoretical and experimental studies have establishedthat the dispersion of a powder depends on the viscosity, surface tension and temperatureof the melt; however, the main factors affecting the fractional composition of the resultingpowders are the pressure and temperature of the energy carrier gas. When non-ferrous metalsand alloys sprayed, designs of nozzles operating on a blast, the temperature of which exceedsthe melting temperature of the sprayed metal by 100-200 °C, have long been used. And whenspraying, for example, heat-resistant alloys, heating of the energy carrier gas up to 400 °C isused. In this case, there is an increase in the dispersion of the obtained microgranules; however,the theoretical prerequisites for this phenomenon are not fully understood. Therefore, theaim of this work was to refine the theoretical concepts of the mechanism of the influence of thetemperature of the gas and melt on the size of the particles obtained. It was found that the dependenceof the particle size on the gas viscosity is rather weak. Calculations show that a twofoldincrease in temperature leads to a decrease in droplet size by about 15%. Therefore, theincrease in the dispersion of microgranules with an increase in the gas temperature or overheatingof the melt can only be explained by a more complete passage of the process of secondarycrushing of drops, which is realized due to a longer stay of the fragments of the melt in hot gas.According to the principle of equivalence, the duration of cooling can be increased in two ways:by heating the metal or by heating the gas. It is shown that when using elevated gas and melttemperatures, the gas mass flow rate decreases to ensure the same sputtering dynamics.